Vagus Nerve Stimulation Therapy for the Treatment of Seizures in Refractory Postencephalitic Epilepsy: A Retrospective Study - Sun, Yulin; Chen, Jian; Fang, Tie; Wan, Lin; Shi, Xiuyu; Wang, Jing; Li, Zhichao; Wang, Jiaxin; Cui, Zhiqiang; Xu, Xin; Ling, Zhipei; Zou, Liping; et al. (Frontiers in Neuroscience, 2021)
Background: Vagus nerve stimulation (VNS) has been demonstrated to be safe and effective for patients with refractory epilepsy, but there are few reports on the use of VNS for postencephalitic epilepsy (PEE). This retrospective study aimed to evaluate the efficacy of VNS for refractory PEE. Methods: We retrospectively studied 20 patients with refractory PEE who underwent VNS between August 2017 and October 2019 in Chinese PLA General Hospital and Beijing Children’s Hospital. VNS efficacy was evaluated based on seizure reduction, effective rate (percentage of cases with seizure reduction ≥50%), McHugh classification, modified Early Childhood Epilepsy Severity Scale (E-Chess) score, and Grand Total EEG (GTE) score. The follow-up time points were 3, 6, and 12 months after VNS. Pre- and postoperative data were compared and analysed. Results: The median (interquartile range [IQR]) seizure reduction rates at 3, 6, and 12 months after VNS were 23.72% (0, 55%), 46.61% (0, 79.04%), and 67.99% (0, 93.78%), respectively. The effective rates were 30% at 3 months, 45% at 6 months and 70% at 12 months. E-chess scores before the operation and at 3, 6, and 12 months after the operation were 10 (10, 10.75), 9 (9, 10), 9 (9, 9.75), and 9 (8.25, 9) (P<0.05), respectively. GTE scores before surgery and at 12 months after the operation were 11 (9, 13) and 9 (7, 11) (P<0.05), respectively. The mean intensity of VNS current was 1.76±0.39 (range: 1.0–2.5) mA. No intraoperative complications or severe post-operative adverse effects were reported. Conclusions: Our study shows that VNS can reduce the frequency and severity of seizure in patients with refractory PEE. VNS has a good application prospect in patients with refractory PEE.